PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL BERBASIS ANDROID TERHADAP HASIL BELAJAR MAHASISWA - Yesi Budiarti; Reni Tantri (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
Audio-visual media is a media that can display elements of images and sound elements in an integrated manner when communicating messages or information. Audio visual media is an intermediary media or the use of material and its absorbers through sight and hearing. Thus building conditions that can make students able to gain knowledge, skills and attitudes. The purpose of this study was to determine "The influence of the use of Android-based audio visual learning media on student learning outcomes". This type of research is a quasi-experimental, with the Non-equivalent Control Group Design experimental design. In sampling using a purposive sampling technique. The population and sample in this study were the fifth semester students of the PGSD Study Program, totaling 139 students. Based on the results of the study that the pre-test and post-test scores in the experimental class get a t-test value of 4.06 and a t-table of 1.70 then 4.06> 1.70. Then this can be said to be greater than t table. Thus it shows that the hypothesis has a positive influence on the use of android-based audio visual media on student learning outcomes. The magnitude of the influence of the use of audio visual media is 36.34%.